The Influence of Capital Adequency Ratio and Loan to Deposit Ratio on Return on Equity at PT. Bank Rakyat Indonesia Tbk - Amthy Suraya (Universitas Negeri Makassar, 2017)
Bank financial performance is a picture of the financial condition of a bank in a certain period, both including aspects of raising funds and channeling funds. The purpose of this study is to examine the effect of Capital Adequency Ratio (CAR) (variable X1) and Loan to Deposit Ratio (LDR) (variable X2) on Return On Equity (ROE) (variable Y). The method used in this research is descriptive analysis method with a quantitative approach. The research object of PT. Bank BRI, Tbk, period 2008-2015. The data source used is the secondary data source and the statistical method used is multiple linear regression analysis for Capital Adequency Ratio (CAR) and Loan to Deposit Ratio (LDR) to Return On Equity (ROE). By testing the classical assumptions first. The results of the study by stimulatory variables Capital Adequency Ratio (CAR) and Loan to Deposit Ratio (LDR) are known to Fcount (51,528)> Ftable (5.79) and the level of significance then the Capital Adequency Ratio (CAR) and Loan to Deposit Ratio (LDR) in a manner Simultaneously has a significant influence on Return On Equity (ROE).